Congenital Anomalies at Birth: A Hospital Based Study in UAE - Aryasinghe, L; Moezzi, D; Ansari, TA; Mathew, E; Sharbatti, SA; Shaikh, RB (Journal of Nepal Paediatric Society, 2012)
Introduction: It is widely acknowledged that congenital anomalies heavily contribute to infant morbidity and mortality worldwide, with an estimated 9 million infants (7% of all births) born annually having a serious congenital anomaly that result in death or lifelong disability. The objective of our study was to estimate the frequency of congenital anomalies at the Gulf Medical College Hospital and Research Center, Ajman and to estimate the proportion of births with congenital anomalies per 1,000 live births. Materials and Methods: It was a Hospital-Record based descriptive study of the 1,222 consecutive live births from December 2007 to June 2008. Results: There were 84 cases of congenital anomalies among the 1,222 live births; the rate of anomalous births was 68.7 per 1,000 live births or 6.9%. Anomalies of the genitourinary system (40.5%) were the most common, followed by musculoskeletal (28.6%) and cardiovascular (10.7%). Gastrointestinal, chromosomal and multiple system anomalies accounted for 3.6% each and miscellaneous anomalies were seen in 7.1%. Central Nervous system (2.4%) anomalies were the least. Congenital hydrocele (19.0%) was seen to have the highest frequency amongst all recorded anomalies, followed by Talipes or Clubfoot (14.3%). 9.3% of the male and 4.3% of the female population of live births had a congenital anomaly. Birth Weight (p=0.005) and Gender (p=0.001) were found to have significant association with the frequency of birth defects. Maternal Age, gravidity, parity, previous abortions, VDRL and Hepatitis B status, Gestational Diabetes, Pregnancy Induced Hypertension, gestational age, maternal and infant blood group, nationality and consanguinity showed no statistically significant association with congenital anomalies. Conclusion: The proportion of congenital anomalies found in our study is alarmingly high and emphasizes the need for more accessible nationwide screening, counseling and surveillance systems. J. Nepal Paediatr. Soc. 32(2) 2012 105-112 doi: http://dx.doi.org/10.3126/jnps.v32i2.5995